The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-81739-x
|View full text |Cite
|
Sign up to set email alerts
|

Plummeting anthropogenic environmental degradation by amending nutrient-N input method in saffron growing soils of north-west Himalayas

Abstract: Nitrous-oxide emission and nitrate addition from agriculture to earth’s environment are two main agriculture related anthropogenic causes of environmental degradation that needs greater attention. For addressing the aforesaid issue, new techniques/practices need to be developed and implemented. The present investigation, which was focused on this issue, resulted in developing a new mode of nitrogen (N) placement, i.e. ‘mid rib placement upper to corms in two splits (MRPU-2S)’, that could reduce nitrous oxide N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In our investigation various modes of nutrient N application showed a significant influence on SOC and its fractions. In treatment MRPU-2S, relatively more SOC was observed that can be attributed to more nitrogen uptake in this treatment due to précised nutrient placement near to corms that resulted in minimum N losses (Sharma et al, 2021), more vegetative growth due to more uptake that further led to increased C retention in plant, which later return to the soil as crop residue or remainder (Aulakh, Khera, Doran, & Bronson, 2001). Besides relatively greater root exudate, due to more nitrogen use efficiency because of localizing N input can also be the reason for relatively more SOC impounding due to the treatment (Christopher & Lal, 2007).…”
Section: Soc and Its Fractionsmentioning
confidence: 88%
See 3 more Smart Citations
“…In our investigation various modes of nutrient N application showed a significant influence on SOC and its fractions. In treatment MRPU-2S, relatively more SOC was observed that can be attributed to more nitrogen uptake in this treatment due to précised nutrient placement near to corms that resulted in minimum N losses (Sharma et al, 2021), more vegetative growth due to more uptake that further led to increased C retention in plant, which later return to the soil as crop residue or remainder (Aulakh, Khera, Doran, & Bronson, 2001). Besides relatively greater root exudate, due to more nitrogen use efficiency because of localizing N input can also be the reason for relatively more SOC impounding due to the treatment (Christopher & Lal, 2007).…”
Section: Soc and Its Fractionsmentioning
confidence: 88%
“…Location A (33 58 0 54 00 N; 74 48 0 03 00 E), B (33 59 0 53 00 N; 74 55 0 51 00 E), C (33 57 0 15 00 N; 74 59 0 30 00 E), and D (33 21 0 08 00 N; 75 45 0 37 00 E), with two sites in each location. The common practice followed by farmers in these locations is either zero nitrogen or 90 kg N ha À1 applied through broadcasting either in one or two splits (Sharma et al, 2021). The saffron corms have the unique characteristic of moving slightly upward every season, so the N input (through urea) was adjusted with the help of a exclusively designed V-shaped single-sided pickaxe (tungroo).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…is being adversely affected by climate change, and agricultural activities leading to emission of methane (CH 4 ), carbon di-oxide (CO 2 ), and nitrous oxide (N 2 O) (Malyan et al, 2021) serve as a major contributing factor to future climate change. The main anthropogenic source of CH 4 (77%) and N 2 O (60%) emissions contributes in Indian Agriculture (Sharma et al, 2021). Methane emissions are confined to rice and enteric fermentation (Kumar et al, 2020b), while CO 2 and N 2 O are uniformly released from all agricultural crops as consequences of crop raising activities such as soil manipulation and fertilizer applications (Kumar et al, 2016a;Kumar et al, 2016b;Bhattacharyya et al, 2018;Sapkota et al, 2021).…”
Section: Introductionmentioning
confidence: 99%